ANALISA PERBANDINGAN HASIL UJI TARIK PADA BEBERAPA SPESIMEN DENGAN LOAD CELL BERKAPASITAS 500 KN - Al Ayubbi, Irfan; Darmanto, Seno; Ariwibowo, Didik (universitas teuku umar, 2022)
Many tensile tests are carried out to complete the basic design information of the strength of a material and as supporting data for material specifications. In the tensile test, the test object is given a load of tensile force that increases continuously, at the same time observations are made regarding the extension experienced by the test object. This study aims to determine the mechanical properties and their changes from a metal to tensile loading using qualitative methods and data collection methods using literature review. The study is carried out by collecting data through a literature book related to the object of the final project. The test results of the material that has the smallest value, namely Aluminum, are obtained, the value without heat treatment is Voltage = 566 N / mm2, Strain = 7.9 , ME = 72.1 N / mm2) and the value using heat treatment is Voltage = 439 N / mm2), Strain = 3.5, ME = 124.5 N / mm2). While the largest value, namely Iron Concrete TP 280, was obtained, the value without heat treatment was Voltage = 1012 N / mm2, Strain = 6.5 , ME = 156.4 N / mm2). While the values when using heat treatment are Voltage = 729 N / mm2), Strain = 3.7, ME =198.8 N / mm2). It can be concluded that the results of the comparative analysis of the strength of the test material without heat treatment and using heat treatment are known when the material is heated until it is close to its critical point, the material will form a new property that will make it change its properties to be tenacious or brittle.Keywords : Tensile Test, Stress, Strain, ME